2011
DOI: 10.1042/cbi20100361
|View full text |Cite
|
Sign up to set email alerts
|

Human platelet lysate supportsex vivoexpansion and enhances osteogenic differentiation of human bone marrow-derived mesenchymal stem cells

Abstract: MSCs (mesenchymal stem cells) with their versatile growth and differentiation potential are ideal candidates for use in regenerative medicine and are currently making their way into clinical trials, which requires the development of xeno-free protocols for their culture. In this study, MSCs were cultured in 10% FCS or 7.5% HPL (human platelet lysate)-supplemented media. We found that both groups of MSCs showed a comparable morphology, phenotype and proliferation. The percentage of cells in the S- and G2-/M-pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 22 publications
(33 reference statements)
7
48
0
Order By: Relevance
“…Platelets lyse was triggered by either, freeze-thaw cycles (1 to 5), ultrasound (63) or chemical treatment (43). HPL presented a high growth factors and cytokines content (74)(75)(76)(77). HPL seemed to be better than FBS for ex vivo MSC expansion (52,72,78,79) since HPL-expanded MSC did not present telomerase shortening (68).…”
Section: Resultsmentioning
confidence: 99%
“…Platelets lyse was triggered by either, freeze-thaw cycles (1 to 5), ultrasound (63) or chemical treatment (43). HPL presented a high growth factors and cytokines content (74)(75)(76)(77). HPL seemed to be better than FBS for ex vivo MSC expansion (52,72,78,79) since HPL-expanded MSC did not present telomerase shortening (68).…”
Section: Resultsmentioning
confidence: 99%
“…PL is considered a perfect candidate for the management of osteoarthritis, mainly due to its ability to promote ex vivo expansion of mesenchymal stem cells (MSCs) used for bone and cartilage engineering (Zaky et al 2008;Chevallier et al 2010;Xia et al 2011;Sofat & Kuttapitiya 2014;Tan et al 2015). MSCs are found in multiple tissues including synovial joints and have shown the potential to differentiate into cells of several tissues including bone and cartilage (Sofat & Kuttapitiya 2014).…”
Section: Discussionmentioning
confidence: 99%
“…When those steps are performed, they proceed to filtration through 0.22 um filters and addition of heparin (2U/ml) to the lysates 35,40,57 . This procedure is the most commonly found in the papers studied, but there are some authors which prefer performing chemical activation instead of thermic/mechanical activation and use of thrombin and/or calcium chloride 7,17,34,41,45,49 .…”
Section: Prp Activation Methodsmentioning
confidence: 99%
“…Besides, PRP did not interfere with osteogenic differentiation and most authors found similar osteogenic differentiation capacity when using one or the other supplement (PRP versus FBS). Albeit few studies have shown that PRP enhanced MSCs osteogenic differentiation in 2D cultures 14,27,35,40 and in 3D cultures 9,22,43 . Interestingly, Hemeda et al 56 found reduced osteogenic differentiation when MSCs where cultured with PRP with high heparine concentrations which were used to avoid PRP clotting.…”
Section: Cell Differentiationmentioning
confidence: 99%